2013
DOI: 10.1007/s13213-013-0783-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial and archaeal diversity in the rumen of Xiangxi yellow cattle (Bos taurus) fed Miscanthus sinensis or common mixed feedstuff

Abstract: Miscanthus sinensis is a potential biofuel that is distributed widely in China, but with difficulties for decomposition and utilization due to the complexity of its fibrous cell walls. To detect whether M. sinensis could increase the population of rumen fibrolitic microbes, two16S rRNA gene libraries were constructed using ruminal samples from Xiangxi yellow cattle fed with either common mixed feedstuff (group C) or M. sinensis (group M), and the diversity of ruminal bacteria and archaea in the rumens of cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…The 98 sequences belonged to the dominion Bacterium, of which approximately 97.96% were related to the Bacteroidetes phylum and only 2.04% of the sequences to the Firmicutes phylum. The predominance of the phyla corroborates data given by several authors who reported that the most relevant identified phyla in bovine rumen are the Bacteroidetes and Firmicutes phyla (Callaway et al, 2010;Chen et al, 2011;Li et al, 2014).…”
Section: Otus Identifiedsupporting
confidence: 88%
“…The 98 sequences belonged to the dominion Bacterium, of which approximately 97.96% were related to the Bacteroidetes phylum and only 2.04% of the sequences to the Firmicutes phylum. The predominance of the phyla corroborates data given by several authors who reported that the most relevant identified phyla in bovine rumen are the Bacteroidetes and Firmicutes phyla (Callaway et al, 2010;Chen et al, 2011;Li et al, 2014).…”
Section: Otus Identifiedsupporting
confidence: 88%
“…The predominant phyla detected in this study were Firmicutes and Bacteroidetes, which is in line with other bovine rumen based studies (De Menezes et al, 2011b;Li et al, 2014;Huws et al, 2016;Van Lingen et al, 2017a). The predominant family-level taxa belonging to Firmicutes in the RF fraction were: Ruminococcaceae, Lachnospiraceae and unclassified Clostridiales.…”
Section: Pyrosequencing Analysissupporting
confidence: 92%
“…The difference in the ability to adapt to a captive environment may result from the different gut bacterial composition of red deer and fallow deer. At the order level, Planctomycetales belongs to Planctomycetes, and Planctomycetes is often found in the digestive tracts of ruminant animals 8 . This taxon possesses the ability to oxidize ammonium 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The significant difference indicated that red deer and fallow deer may have different decomposition abilities for different types of fibers, fats, and proteins. The CPla-4 termite group belongs to Planctomycetes, and the function may be correlated with reducing the concentration of ammonium in the intestinal system 8 . Anaeroplasma has enzymic activity in the Embden-Meyerhof-Parnas pathway for glycolytic catabolism 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation